The Role of Social Responsibility in Company Strategy - Andrija Baric\' (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2022)
Social responsibility is an irreplaceable concept in the modern global economic network. As the concept of social responsibility "matured" in business and science, an increasing number of investors have recognized the benefits of conducting socially and environmentally conscious business and are encouraging the management and other stakeholder groups to implement socially responsible activities to achieve strategic goals. Strategic implementation of socially responsible activities opens up the space for creating a market position that competitors can hardly reach. They would have to successfully imitate the whole spectrum, not just a single socially responsible activity. This paper aims to discuss the relationship between the implementation of social responsibility and company strategy in light of previous research. Sustainable competitive advantage and a positive business result stem from a quality strategy adhered to by all organizational levels in the company. A good link between corporate strategy and the concept of social responsibility is a prerequisite for achieving long-term business sustainability in the global economic network. Based on the above, social responsibility is considered an important strategic element.
Keywords: O32; O33; G34; 330; corporate social responsibility; company strategy; stakeholders; differentiation; identity